Global Reading, Problem-Solving, and Support Reading Strategies Across Worry, Emotionality, and Task-Generated Interference of Learners as Predictors of Reading Comprehension - Bagus Putra Krisdiana (Journal of English for Academic and Specific Purposes)
This research was conducted to investigate partially and simultaneously significant contributions between global reading, problem-solving, support reading, worry, emotionality, and task-generated interference to reading comprehension and the dominant predictor variable to reading comprehension with 540 learners at UIN Maulana Malik Ibrahim Malang. With the Multiple Linear Regression analysis, this study administered a reading comprehension test, SORS, and FLRAS questionnaires to collect the data. The results of the statistical calculation showed that t values of global reading (4.549), problem-solving (4.415), support reading (4.667), worry (2.721), emotionality (2.596), and task-generated interference (2.955) in which all were higher than t table (1.964), so there is a partially significant contribution between all of the predictor variables to reading comprehension. This study used the Multiple Linear Regression analysis to gather data by administering the SORS, FLRAS questionnaire, and reading comprehension test. The statistical analysis revealed a partially significant contribution between all predictor variables to reading comprehension, with t-values for global reading (4.549), problem-solving (4.415), support reading (4.667), worry (2.721), emotionality (2.596), and task-generated interference (2.955) all surpassing the t-table (1.964). A simultaneously significant contribution to reading comprehension was made by global reading, problem-solving, support reading, worry, emotionality, task-generated interference, and the computed F value of 18.195, which was higher than the F table (2.116). In addition, if the Standardized Coefficients Beta column was observed, the dominant variable in reading anxiety was task-generated interference, which had the highest value (.117) in reading anxiety, and the dominant variable in reading strategies, which was support reading, which also had the highest value (.187) of all predictor variables.